(untitled) (IMT INTERNATIONAL JOURNAL OF THE ARTS AND SCIENCES, 2025)
This study investigated the predictors of consumer choice of noodle brands in Enugu State. The specific objectives of the study were to determine the effect of prices, brand image, brand name, brand availability, and advertising on consumers ‘choice of noodle brands in Enugu State. To achieve these objectives, research questions and hypotheses were raised. A descriptive survey research was conducted and survey research design was adopted. Convenience and purposive sampling techniques were used to select a sample of 325 consumers from the population of consumers of noodle brands in Enugu State. A well- structured self-administered questionnaire was used for collection of data from the respondents. Correlation statistical tool was used for data analysis supported by Statistical Package for Social Sciences (SPSS. 22.0). The following findings were observed: that there was a significant effect of the predicting variables understudy including prices, brand image, brand name, brand availability, and advertising on consumers’ choice of noodle brands in Enugu State.It was concluded among others that the study has achieved its objective of establishing the extent to which these predicting factors affect consumers’ choice of noodle brands in Enugu State. Hence, the study recommended that brand managers, and top management of noodle producing and marketing organizations should key into the predicting factors to ensure improvement in consumers’ choice of their noodle brands in Enugu State.